2017
DOI: 10.1002/lary.27017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adult unilateral hearing loss and hearing aid use in the United States

Abstract: 2. Laryngoscope, 128:1681-1686, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 33 publications
4
66
0
3
Order By: Relevance
“…Regarding the time of use (Table 5), the vast majority of the subjects evaluated in this study would not be using hearing aids, even presenting complaints related to UHL, speech recognition benefit, selfperception of improvement in daily communicative skills and satisfaction in most situations with the use of the hearing aid. These results corroborate those found by other researchers 37 who investigated the prevalence of UHL and the use of hearing aids in this population in the United States, who observed that only 11% of this population would use hearing aids.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the time of use (Table 5), the vast majority of the subjects evaluated in this study would not be using hearing aids, even presenting complaints related to UHL, speech recognition benefit, selfperception of improvement in daily communicative skills and satisfaction in most situations with the use of the hearing aid. These results corroborate those found by other researchers 37 who investigated the prevalence of UHL and the use of hearing aids in this population in the United States, who observed that only 11% of this population would use hearing aids.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study conducted in South Korea, the prevalence of UHL determined via KNHANES data was 4.91%. This is lower than the prevalence of 7.9%-13.3% in the general population [17,18] and the prevalence of UHL was 7.2% in the US [13]. Although it was not possible to distinguish SNHL from conductive hearing loss, most patients with UHL had normal tympanic membranes and it was concluded that most of them had SNHL.…”
Section: Discussionmentioning
confidence: 71%
“…Those studies were based on patients aged > 50 years or 40 years with bilateral hearing loss, whereas the participants in the current study were aged � 12 years. Golub et al [13] reported that the prevalence of hearing aid use in people with UHL was 2.0% in the USA and that the reason why it was much lower than that in people with bilateral hearing loss was unawareness of disability. Public health insurance systems may also affect hearing aid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a fim de proporcionar novamente ao paciente a audição binaural, em casos de PAUn, o uso de prótese auditiva é recomendado para aqueles indivíduos que apresentam dificuldades de integração social e/ou profissional e audição residual passível de amplificação 9 . No entanto, a indicação da prótese auditiva para esta população é algo complexo, multifatorial e singular, representando assim um desafio para os profissionais envolvidos no processo de reabilitação auditiva 10,11 .…”
Section: Introductionunclassified